Building bridges takes time: Views of healthcare professionals on health literacy and migration. (13th November 2019) - Baumeister, A; Aldin, A; Chakraverty, D; Seven, ÜS; Anapa, G; Jakob, T; Skoetz, N; Kalbe, E; Woopen, C
Abstract: Background: Health literacy is an output of individual resources and capabilities, situational factors, environmental conditions, and the requirements of the health care system. As migration continues to increase globally, successful interaction between healthcare professionals and migrants can be important for a sustainable and resource-oriented promotion of health literacy. This study aims to explore challenges, needs and applied solutions of healthcare professionals in the interaction with migrants in Germany. Methods: Five focus group discussions were conducted in Cologne, Germany. Participants were healthcare professionals (n = 30), including general practitioners, medical specialists in inpatient and outpatient care, and nurses. Discussions were audio recorded, transcribed verbatim and analysed by qualitative content analysis. Preliminary results: Participants reported a lack of time and general uncertainty in dealing with the health literacy-related needs of the target population. Assumptions on discrimination through the health system and restrictive gender roles on the patients' side were additional key challenges for a successful interaction. To bridge these barriers, some participants reported to invest time even beyond systemic conditions; most wished for professional interpreters or cultural mediators. Participants who themselves were migrants found this helpful for communicating information to patients and improving patients' confidence in the recommended treatment. Using clinical staff as lay interpreters outside their own treatment situation was rated critical, as it can be associated with a considerable burden due to a further time restriction for their actual tasks. Conclusions: Preliminary findings reveal that general problems in the health care setting (e.g. time pressure, ensuring patients' compliance) can occur more intensively in migrant patients. Health professionals require support through the provision of state-funded professional interpreters. Key messages: Health literacy related challenges become more visible in the context of migration and reveal general issues in the German health system that need to be solved for the benefit of the entire population. Research on health literacy in the context of migration is important in order to ensure the promotion and maintenance of health equally and effectively across populations.